p53-dependent regulation of mitochondrial energy production by the RelA subunit of NF-κB - Johnson, Renée F (2011)
Aberrant activity of the NF-κB transcription factor family, which regulates cellular responses to stress and infection, is associated with many human cancers. In this study, we define a function for NF-κB in regulation of cellular respiration that is dependent upon the tumor suppressor p53. Translocation of NF-κB family member RelA to mitochondria was inhibited by p53 by blocking an essential interaction with the heat shock protein Mortalin. However, in the absence of p53, RelA was transported into the mitochondria and recruited to the mitochondrial genome where it repressed mitochondrial gene expression, oxygen consumption and cellular ATP levels. We found mitochondrial RelA function to be dependent on its conserved C-terminal transactivation domain and independent of its sequence specific DNA binding ability, suggesting that its function in this setting was mediated by direct interaction with mitochondrial transcription factors. Taken together, our findings uncover a new mechanism through which RelA can regulate mitochondrial function, with important implications for how NF-κB activity and loss of p53 can contribute to changes in tumor cell metabolism and energy production.